The Influence of Social Intelligence and Altruism on Work Ethic of Homeroom Teachers at Junior High School - Mahmudah Mahmudah; M Nur Mustafa; Daeng Ayub Natuna (STAI Hubbulwathan Duri, 2023)
This study aimed to determine the effect of social intelligence and altruism on the homeroom teacher's work ethic This study used a quantitative approach with the ex post facto method, the study population was 120 homeroom teachers at Public Middle School, and the study sample was 92 homeroom teachers using a simple random sampling technique. Data collection techniques were carried out using questionnaires and distributed via the Google form. Meanwhile, data analysis was carried out using inferential statistical analysis techniques consisting of classic assumption tests and hypothesis testing with the help of SPSS (statistical package for social science) version 22. The findings revealed a significant and positive influence of social intelligence and altruism on the work ethic of the homeroom teacher. The magnitude of the effect is 28.1%, with a low interpretation because the remaining 71.9% is determined by factors outside the scope of this study. The greater the homeroom teacher's work ethic, the greater the homeroom teacher's social intelligence and altruism.